Cytotoxicity Effects of Miltefosine and Niosomal form on Human Umbilical Vein Endothelial Cells: Colorimetric Assay, Apoptosis, and Gene Expression Profiling - Sharifi, Fatemeh; Seyedi, Fatemeh; Mohamadi, Neda; Sharifi, Iraj; Pardakhty, Abbas; Khosravi, Ahmad; Kamali, Ali (Letters in Drug Design & Discovery, 2023)
Background: Miltefosine (MIL), hexadecyl phosphocholine, is the only oral medicine used to treat leishmaniasis. This drug has a major limitation and is expensive and potentially teratogenic. Objective: This study aimed to evaluate the toxic effect of MIL and its niosomal form on human umbilical vein endothelial cells (HUVECs), the expression genes, and the profile associated with apoptosis in the mitochondrial permeabilization regulated. Methods: Miltefosine niosome (MN) prepared by the thin-film hydration method and characterized. HUVECs were treated with MIL (100–1000μg/ml), and MN (10-50μg/ml) for 24, 48, and 72 h, and the persistence was assessed by colorimetric assay flow cytometry and real-time PCR. Results: Lesser toxicity was detected on cell proliferation for MN while both forms decreased Bcl-2 and elevated the expression of Bak/Bax and caspases-3, -8, and -9. The data demonstrated that MIL significantly exerted its cytotoxicity on HUVECs compared to MN. Conclusion: This drug should be considered embryotoxic during pregnancy, while in niosomal form, it released slowly and remained safe. The mechanism of action of MIL associated with programmed cell death.
Keywords: Miltefosine